Ameliorating effect of pomegranate juice consumption on carbon tetrachloride-induced sperm damages, lipid peroxidation, and testicular apoptosis - Türk, Gaffari; Çeribaşı, Songül; Sönmez, Mustafa; Çiftçi, Mehmet; Yüce, Abdurrauf; Güvenç, Mehmet; Özer Kaya, Şeyma; Çay, Mehmet; Aksakal, Mesut (My University, 2016)
The aim of this study was to investigate whether pomegranate juice (PJ) consumption has an ameliorating effect on carbon tetrachloride (CCl4)-induced sperm damages and testicular apoptosis associated with the oxidative stress in male rats. The study comprised of four groups (groups 1–4). Group 1 received olive oil ? distilled water daily; group 2 was treated with 5 ml/kg PJ ? olive oil daily; group 3 was treated with 0.25 ml/kg CCl4 dissolved in olive oil, weekly ? distilled water daily; and group 4 received weekly CCl4 ? daily PJ. All administrations were performed by gavage and maintained for 10 weeks. CCl4 administration caused significant decreases in body and reproductive organ weights, sperm motility, concentration and testicular catalase activity, significant increases in malondialdehyde (MDA) level, and abnormal sperm rate and apoptotic index along with some histopathological damages when compared with the control group. However, significant ameliorations were observed in absolute weights of testis and epididymis, all sperm quality parameters, MDA level, apoptotic index, and testicular histopathological structure following the administration of CCl4 together with PJ when compared with group given CCl4 only. In conclusion, PJ consumption ameliorates the CCl4-induced damages in male reproductive organs and cells by decreasing the lipid peroxidation.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Apoptosis; carbon tetrachloride; lipid peroxidation; pomegranate juice; sperm; testis